2016
DOI: 10.1021/acsnano.6b06104
|View full text |Cite
|
Sign up to set email alerts
|

Analgesic Microneedle Patch for Neuropathic Pain Therapy

Abstract: Neuropathic pain caused by nerve injury is debilitating and difficult to treat. Current systemic pharmacological therapeutics for neuropathic pain produce limited pain relief and have undesirable side effects, while current local anesthetics tend to nonspecifically block both sensory and motor functions. Calcitonin gene related peptide (CGRP), a neuropeptide released from sensory nerve endings, appears to play a significant role in chronic neuropathic pain. In this study, an analgesic microneedle (AMN) patch w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
84
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 121 publications
(85 citation statements)
references
References 58 publications
1
84
0
Order By: Relevance
“…In the present study, hierarchical cluster analysis was used to divide SNI rats into two clusters: one group (approximately 68%; anhedonia-like phenotype) with reduced sucrose preference in the SPT and the other (approximately 32%; without anhedonia-like phenotype) with sucrose preference similar to that in sham-operated rats, consistent with our previous report ( Fang et al, 2018 ). In the current study, we also found that rats, regardless of the presence or absence of anhedonia-like phenotype, exhibited similar MWT scores, suggesting that alterations in mood-related behaviors were independent of the degree of nociceptive damage, which was consistent with previous studies ( Monassi et al, 2003 ; Austin and Moalem-Taylor, 2010 ; Austin et al, 2015 ; Gui et al, 2016 ; Xie et al, 2017 ; Fang et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…In the present study, hierarchical cluster analysis was used to divide SNI rats into two clusters: one group (approximately 68%; anhedonia-like phenotype) with reduced sucrose preference in the SPT and the other (approximately 32%; without anhedonia-like phenotype) with sucrose preference similar to that in sham-operated rats, consistent with our previous report ( Fang et al, 2018 ). In the current study, we also found that rats, regardless of the presence or absence of anhedonia-like phenotype, exhibited similar MWT scores, suggesting that alterations in mood-related behaviors were independent of the degree of nociceptive damage, which was consistent with previous studies ( Monassi et al, 2003 ; Austin and Moalem-Taylor, 2010 ; Austin et al, 2015 ; Gui et al, 2016 ; Xie et al, 2017 ; Fang et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…Microneedle patch vaccines can be used to target not just infectious viruses but also cancer, and microneedle patch‐assisted delivery of anti‐cancer immunotherapeutic agents have been developed (Ita, ). A range of drugs, such as analgesics or medication for dementia, could be delivered by microneedle patch (Kathuria et al, ; Kearney et al, ; Xie et al, ). In the field of dermatology, several reports have shown that the active cosmetic ingredients, such as retinoic acid and ascorbic acid, can be loaded onto the microneedle patch, and these cosmetic patches were found to be safe and effective for pigmented lesions or wrinkles (Hirobe, Otsuka, & Iioka, ; Kim, Yang, Kim, & Jung, ; Lee, Yang, & Kim, ).…”
Section: Discussionmentioning
confidence: 99%
“…Microneedle patches have been used for transdermal delivery in different medical fields (Hirobe, Azukizawa, & Hanafusa, ; Kearney, Caffarel‐Salvador, Fallows, McCarthy, & Donnelly, ; Wang, Ye, & Hochu, ; Xie, Pascual, & Lieu, ). To increase the permeability of active agents such as drugs or vaccines across skin, the formulation of microneedle patches has been technologically developed (Kathuria, Li, & Pan, ; Lau, Fei, Liu, Chen, & Liu, ).…”
Section: Introductionmentioning
confidence: 99%
“…Fabrication of Microneedle Patch : The fabrication of microneedle was conducted by following the protocol published in this paper . In brief, ≈2 mg Cy5 (gift from Dr. Zhang lab at Cedars‐Sinai, CA) was dissolved in 500 µL 8% (w/w) sodium carboxylmethyl cellulose (SCMC, Sigma‐Aldrich, MO, USA) solution.…”
Section: Methodsmentioning
confidence: 99%